1997
DOI: 10.1007/s003300050276
|View full text |Cite
|
Sign up to set email alerts
|

Fast spin echo vs conventional spin echo in cervical spine imaging

Abstract: The major attraction of fast-spin-echo (FSE) imaging is reduced acquisition time; however, careful review of the literature reveals many weaknesses: phase-encoded blurring, truncation artefact, bright fat signal, reduced magnetic susceptibility and increased motion artefact. Our aim was a prospective, blinded comparison of FSE and conventional spin echo (CSE) in the cervical spine. Both sequences were performed in 43 patients (19 males and 24 females; mean age 45 years, range 15-66 years). Twenty-eight patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Use of the GRE sequence is debated, as it is very sensitive to motion, especially with breathing. It might miss smaller amount of blood or hemosiderin (Gillams et al, 1997;Katz et al, 1989).…”
Section: Mri Sequencesmentioning
confidence: 99%
“…Use of the GRE sequence is debated, as it is very sensitive to motion, especially with breathing. It might miss smaller amount of blood or hemosiderin (Gillams et al, 1997;Katz et al, 1989).…”
Section: Mri Sequencesmentioning
confidence: 99%
“…There seems to be no published data on this subject until Campell et al (16) reported a study including a limited number of patients claiming that chemical-shift imaging may be a useful screening tool and adjunct to traditional MR imaging sequences. There are a number of studies focusing on rapid spinal imaging (1,3,17) that either reduce the number of sequences in conventional protocols or assess newer sequences generated using parallel imaging technology.…”
Section: Discussionmentioning
confidence: 99%
“…The lower scores of the neural elements of the lumbar spine were frequently seen in elderly patients having severe spondylosis, unfortunately, these patients could benefit the most from the faster scans. GRE sequences are known to cause higher magnetic susceptibility, which becomes evident during motion as well as at osteophytes-cerebrospinal fluid (CSF) or osteophytes-soft tissue interfaces in spondylotic patients (3,20). This increased the magnetic susceptibility sensitivity of GRE results in image degradation, especially blurring of the neural foramina when spondylotic changes are present, and as a result, overestimation of both canal and foraminal stenosis occur.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern is the detection of small low-signal-intensity hemosiderin-containing lesions [73], since the sensitivity to magnetic suscep- Fig. Turbo spin echo is not only applied routinely to the brain [74] but also to the spine [75,76], to the pediatric brain and spine, and to the inner ear [77±80], as a 2D as well as 3D version. GRASE, gradient and spin echoes.…”
Section: The Spin-echo Groupmentioning
confidence: 99%